Style and the “Idea” of the sophist after Plato : the impact of form typology on sophistic teaching and writing on interdisciplinary scholarly work - Haase, Fee Alexandra (Sapientia, 2008)
After the First Sophistic sophists acted among the scholars in the Mediterranean in many regards as a distinct group. Since many examples show that they were not only performing sophists, but they were persons engaged in other activities, we will examine here several cases of similarities and differences between them and other groups of scholars. Our three basic questions ‘what, how and why did the sophists teach and write?’ We try to answer examining diachronically the major forms and genres of writings they produced (‘What’), the ‘How’ we answer looking at their sophistic performance as a communicative activity beyond borders of contemporary disciplines, and the ‘Why’ we try to answer emphasizing the necessity of sophistical activity in the contemporary socialization and education in antiquity. Claiming that style was the idea of the sophists, we put Plato’s concept of idea critically in the context of the concept of the idea derived from contemporary and later sophists of the Second Sophistic focusing on the function of visuality expressed in their concept of idea from early sophistic works in the time of Plato and later contributions.